Correlating Electrolyte Inventory and Lifetime of HT-PEFC by Accelerated Stress Testing. Issue 12 (1st January 2015) - Eberhardt, S. H.; Lochner, T.; Büchi, F. N.; Schmidt, T. J.
Abstract : Phosphoric acid electrolyte evaporation in a polybenzimidazole based high temperature polymer electrolyte fuel cell is analyzed as a function of reactant gas stoichiometry and temperature. Based on these results a phosphoric acid vapor pressure curve is derived to predict the fuel cell liftetime with respect to electrolyte inventory. The predicted fuel cell life was validated by means of an accelerated stress test. Additionally, the correlation between electrolyte inventory and fuel cell performance was investigated by recording H2 /air and H2 /O2 polarization curves during the course of the stress test to gain insight into the relation between acid inventory and the different degradation modes.